Patient perspectives on intraoperative blood transfusion: A qualitative interview study with perioperative patients. Issue 2 (10th January 2023) - Lenet, Tori; Skanes, Stephanie; Tropiano, Joseph; Verret, Michael; McIsaac, Daniel I.; Tinmouth, Alan; Hallet, Julie; Nicholls, Stuart G.; Fergusson, Dean A.; Martel, Guillaume
Abstract: Background: While red blood cell (RBC) transfusions are frequently administered during surgery, little is known about patient perspectives regarding intraoperative transfusion. The aim of this study was to understand patient perspectives about intraoperative RBC transfusion and explore their willingness to engage in transfusion prevention strategies. Study Design and Methods: This descriptive qualitative study used semi‐structured patient interviews before and after surgery. Purposive sampling was used to select adult patients with varying perioperative courses, including having perioperative transfusion or postoperative anemia. Inductive and deductive thematic analyses were conducted to identify themes. Results: Twenty patients (nine preoperative and 11 postoperative patients) were interviewed. The following themes were identified: Risk–benefit perception of transfusion, transfusion acceptance, trust, patient involvement in transfusion decisions, acceptance of transfusion prevention interventions, and communication. Patients perceived transfusions as low‐risk compared to the surgery itself. Factors influencing transfusion acceptance included trust in the healthcare system and the perception of the treatability of transfusion‐related complications. Some patients preferred to defer transfusion decision making to the perioperative team, citing trust in professional judgment and building a positive relationship with their surgeon. Others wished for their preferences to be incorporated into transfusion decisions. Some desired detailed blood consent conversations and most were willing to participate in strategies to reduce intraoperative transfusion. Conclusion: In our sample, patients consider intraoperative transfusions as low‐risk high‐reward interventions and trust the healthcare system and perioperative team to guide intraoperative transfusion decision making. However, preoperative transfusion consent discussions were recalled as being superficial and lacking nuance. Targeted strategies are required to improve blood consent discussions to better integrate patient preferences.